Left-Right Facial Orientation of Familiar Faces: Developmental Aspects of « the Mere Exposure Hypothesis » - Amestoy, Anouck; Bouvard, Manuel P.; Cazalets, Jean-René (Frontiers in Psychology, 2010)
We investigated the developmental aspect of sensitivity to the orientation of familiar faces by asking 38 adults and 72 children from 3 to 12 years old to make a preference choice between standard and mirror images of themselves and of familiar faces, presented side-by-side or successively. When familiar (parental) faces were presented simultaneously, 3–5 year-olds showed no preference, but by age 5-7 years an adult-like preference for the standard image emerged. Similarly, the adult-like preference for the mirror image of their own face emerged by 5-7 years of age. When familiar or self faces were presented successively, 3–7 year-olds showed no preference, and adult-like preference for the standard image emerged by age 7-12 years. These results suggest the occurrence of an early developmental process in the perception of familiar face asymmetries which is retained in memory related to knowledge about faces.